Ecopedagogies : practical approaches to experiential learning - Bayer, Ellen; Finley, Judson Byrd. (Abingdon : Routledge, 2023)
Ecopedagogies showcases a range of creative approaches that educators across multiple disciplines use to empower students to access and engage with nature, an increasingly important consideration in a post-COVID world in environmental crisis. The volume includes chapters written by scholars from the environmental arts and humanities, literature, writing studies, rhetoric, music, religious studies, environmental studies and sustainability, sociology and anthropology, physical education, and outdoor education. Each author walks the reader through the details of how their ecopedagogy works, identifies potential challenges while also detailing how to address them, and explains the rewards to students, instructors, and more-than-human nature that they have witnessed through the use of these approaches. The contributions represent diverse types of academic institutions, offering broad applicability to instructors, including community colleges, private liberal arts colleges, and large state, regional, public, and private universities. The book explores a series of key questions about how educators can facilitate meaningful learning experiences with the natural world, inside and outside the classroom, and it looks at how to foster inclusivity, navigate problems with access, and explore intersections with environmental justice. As a practical guide, the book delivers a well-provisioned toolbox containing exercises, activity guides, and assignments for those teaching environmentally focused college courses.
Includes index.
Keywords: Environmental education; Experiential learning; Active learning; EDUCATION / Curricula; EDUCATION / Teaching Methods & Materials / General; EDUCATION / Teaching Methods & Materials / Arts & Humanities